2013
DOI: 10.1093/jscr/rjs039
|View full text |Cite
|
Sign up to set email alerts
|

Upper limb gangrene following intramuscular diclofenac: a rare side effect

Abstract: Diclofenac is a very commonly used analgesic medication. Diclofenac is a non-steroidal anti-inflammatory drug and acts by inhibiting COX (cyclo-oxygenase) 1 and 2. It has both analgesic and anti-pyretic effects. It can be administered both orally and parentarelly. Among the many side effects of diclofencac, extensive ganrene of the extremities is never reported as one of the probable complications. Extensive PubMed and other literature searches did not reveal any previously reported case reports, hence the rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 4 publications
0
11
1
Order By: Relevance
“…The chance‐adjusted agreement between the two investigators on the application of the inclusion and exclusion criteria was 0.88. A total of 45 eligible reports 6‐50 published between 1996 and 2019 in English (N = 44) or Spanish (N = 1) were identified. The reports were primarily (N = 41, 91%) from Europe (Turkey, N = 17; Italy, N = 4; Belgium, N = 1; Germany, N = 1; Switzerland, N = 1) and Asia (India, N = 9; South Korea, N = 5; China, N = 1; Israel, N = 1; Qatar, N = 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chance‐adjusted agreement between the two investigators on the application of the inclusion and exclusion criteria was 0.88. A total of 45 eligible reports 6‐50 published between 1996 and 2019 in English (N = 44) or Spanish (N = 1) were identified. The reports were primarily (N = 41, 91%) from Europe (Turkey, N = 17; Italy, N = 4; Belgium, N = 1; Germany, N = 1; Switzerland, N = 1) and Asia (India, N = 9; South Korea, N = 5; China, N = 1; Israel, N = 1; Qatar, N = 1).…”
Section: Resultsmentioning
confidence: 99%
“…The aforementioned 45 reports included 62 previously healthy subjects (40 females and 22 males aged from 13 to 81, median 57 years) with Nicolau syndrome occurring after intramuscular 6‐11,13‐50 or local 12 injection of a non‐steroidal anti‐inflammatory drug, as shown in Table 1. The vast majority of cases (N = 53; 85%) occurred following administration of diclofenac.…”
Section: Resultsmentioning
confidence: 99%
“…Although drugs such as penicillin, promethazine, Vitamin B complexes, diclofenac had been implicated in a few instances, extensive search of literature could not reveal ceftriaxone as an offender. [ 1 2 3 4 ] Authors presume that it was an inadvertent intra-arterial or periarterial injection which could be possible in case of administration to the medial aspect of the thigh. Postinjection ischemic gangrene may result from direct vascular injury, perivascular inflammation or vasoconstriction from the unintentional intra-arterial injection.…”
Section: Discussionmentioning
confidence: 99%
“…Femoral artery thrombosis is an unusual complication after IM injection which might lead to a serious complication like limb gangrene. [ 1 2 3 4 ] Here, we report a case of a 12-month-old boy, presented with ischemic limb and digital gangrene 3 days after a misplaced IM injection of ceftriaxone by a local practitioner.…”
Section: Introductionmentioning
confidence: 99%
“…Upper limb gangrene commonly occurs as a result of fracture mismanagement by traditional bone setters (TBS) or in humeral head or neck fractures [1][2][3]. Less common causes include vascular cannulation for dialysis, arteriography, thrombolysis, arthroscopy of the shoulder joint, following intravenous injection of drugs and infections such as gas gangrene [4][5][6]. Rarely it is found as a consequence of trauma and one study found that serious distal ischemia is uncommon in upper limb injuries resulting from trauma [7].…”
Section: Introductionmentioning
confidence: 99%